Disparities in the provision of aging-friendly communities in old and new urban neighborhoods in China. Issue 7 (2nd April 2019) - Yu, Jingyu; Ma, Guixia; Cai, Shaoxing
Abstract : Purpose: Aging-friendly environments have been encouraged to develop at the city level, district level and community level in China. In the process of rapid urbanization, the state of aging-friendly communities in old and new neighborhoods is disparate. Hence, the purpose of this paper is to investigate aging-friendly communities and identify the disparities in old and new neighborhoods. Design/methodology/approach: A total of 1, 172 elderly respondents completed the survey. Of these, 576 seniors lived in an old community developed before 2000, and 596 lived in a new community developed after 2000. In total, 17 physical environment factors and 10 social environment factors were identified. Findings: The results indicated that public spaces, facilities and transportation in old neighborhoods were inferior to those in new neighborhoods. Most social environment factors in new neighborhoods achieved higher satisfaction levels than those in old neighborhoods. The satisfaction levels of aging-friendly community factors in both old and new neighborhoods were below the expectation levels of elders. Practical implications: In order to improve physical aging-friendly environments in old neighborhoods, it is suggested that full use is made of school facilities and the renovation of old buildings. The locations of public transportation stations in new neighborhoods are recommended to be revised within 5-min walking distances of senior residents. Both old and new neighborhoods are encouraged to improve social aging-friendly environments by increasing the coverage of medical services and creating multiple approaches to recreation activities. Originality/value: These findings have empirical significance for urban planners and policy makers, in regard to identifying disparities between old and new neighborhoods, and understanding the equitable allocation and distribution of urban resources.